2019
DOI: 10.1039/c9ra06219j
|View full text |Cite
|
Sign up to set email alerts
|

CVD controlled growth of large-scale WS2 monolayers

Abstract: Monolayer tungsten disulfide (WS2) with a direct band gap of ca. 2.0 eV and stable properties has been a hotspot in two-dimensional (2D) nanoelectronics and optoelectronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
1
17
0
1
Order By: Relevance
“…The advantage of WCl 6 compared to the powder-based method is much better scalability, and the advantage over the MOCVD films is the much shorter deposition time. FWHM values for films grown on sapphire substrates from a W(CO) 6 precursor range from 27 to 65 meV [27,34,[70][71][72], and span 21-68 meV when WO 3 powder is used as a precursor [7,20,23,[73][74][75]. Our FWHM value is an improvement on values (67 meV) reported by Park et al [26] who also employed gasphase CVD with a WCl 6 precursor.…”
Section: Resultssupporting
confidence: 49%
“…The advantage of WCl 6 compared to the powder-based method is much better scalability, and the advantage over the MOCVD films is the much shorter deposition time. FWHM values for films grown on sapphire substrates from a W(CO) 6 precursor range from 27 to 65 meV [27,34,[70][71][72], and span 21-68 meV when WO 3 powder is used as a precursor [7,20,23,[73][74][75]. Our FWHM value is an improvement on values (67 meV) reported by Park et al [26] who also employed gasphase CVD with a WCl 6 precursor.…”
Section: Resultssupporting
confidence: 49%
“…Various groups have investigated synthesis scalability by varying parameters, such as temperature, gas flow, environment (gas mixtures), pressure (low and atmospheric), catalyzer (sodium, terephthalic acid, etc. ), growth time, precursor amount and substrate cleaning [18][19][20][21][22][23][24][25][26][27][28][29][30]. These studies demonstrated divergent results even between similar growing conditions, leaving researchers puzzled about why this occurs.…”
Section: Introductionmentioning
confidence: 99%
“…There are two peaks centred at 253 and 632 cm −1 , which are due to Cu 3 P [9,27]. The frequency difference between the two peaks is constant, unlike Van Der Waals two-dimensional materials, such as graphene, hexagonal boron nitride and molybdenum sulfide, of which the frequency difference is a function of the film thickness [28]. Therefore, the frequency difference cannot be utilized to determine the thickness of Cu 3 P film.…”
Section: Resultsmentioning
confidence: 99%